Analisis Efektivitas Predikat Wilayah Birokrasi Bersih Melayani (Wbbm) Terhadap Peningkatan Kualitas Pelayanan Pas Bandara Kantor Otoritas Bandar Udara Wilayah III - Erlita Nazla Pangestika; Gallis Nawang Ginusti (Journal of Creative Student Research, 2023)
The Office of the Airport Authority Region III is one of the government agencies that provide public services to the public, namely airport PAS services, therefore the Office of the Airport Authority Region III participates in the government program to build a good and clean government by designing the construction of an integrity zone towards a Serving Free Bureaucratic Area (WBBM) to improve the quality of its services. The purpose of this research is to determine the effectiveness of the WBBM predicate and the supporting and inhibiting factors in improving the quality of airport PAS services at the Office of the Airport Authority Region III. The research method used is mixed methods, which means combining quantitative and qualitative research simultaneously with the chosen strategy, namely sequential explanatory. The data sources obtained are primary and secondary data with the data collection techniques used are interviews, documentation, and direct observation at the Region III Airport Authority Office. The results of this study indicate that the WBBM predicate is effective in improving the quality of airport PAS services as evidenced by the SKM results which continue to increase from 2020 to 2022 and changes in the airport PAS service system to online services. Factors that support the improvement of the quality of airport PAS services are the six areas of change in WBBM and the existence of inhibiting factors, namely websites that have not been properly managed, human resources that have not provided excellent service, and lack of work ethic in providing services